Preoperative factors influencing surgical site infections (SSIS) in inguinal hernia patients undergoing tension-free mesh hernia repair at regional public hospitals in Bali - Putu Anggia Dimitri Pramesti; Made Dharmesti Wijaya; Made Dwi Yoga Bharata (Intisari Sains Medis, 2021)
Introduction: Surgical site infection (SSI) is the most common nosocomial infection, affecting one out of three patients undergoing surgical procedures. The incidence of SSI in clean surgical wounds is still higher, especially in inguinal hernia repair. Today, tension-free mesh hernia repair is the primary method used in inguinal hernia management to reduce the risk of recurrence. This study aims to analyze preoperative factors influencing the incidence of SSIs in inguinal hernia patients that underwent tension-free mesh hernia repair at several regional public hospitals in Bali.Methods: This is a case-control study with samples taken from seven regional hospitals in Bali. Data used in this study were obtained from patients’ medical records from 2017-February 2021. Samples included in this study are inguinal hernia patients that underwent tension-free mesh hernia repair and postoperative check-up. Samples are selected through the purposive sampling method. Statistical analysis was done using SPSS 18.0 software. Univariate and bivariate analysis was performed, and Pearson chi-square and Fisher’s exact test were applied.Results: From the 61 samples in the case group and 61 samples in the control group, the results showed a significant relationship between the incidence of SSIs and elderly patients (OR = 2.262, 95% CI 1.086-4.711), between SSIs and obesity (OR = 9.057, 95% CI 1.096-74.808), and between SSIs and diabetes mellitus (OR = 9.620, 95% CI 2.094-44.201).Conclusion: It is concluded that there is a significant relationship between these preoperative factors and the incidence of SSIs in inguinal hernia patients that underwent tension-free mesh hernia repair at seven regional public hospitals in Bali.